2009
DOI: 10.1007/s10549-009-0472-4
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant (ICI 182,780) sensitizes breast cancer cells expressing estrogen receptor α to vinblastine and vinorelbine

Abstract: Cumulative data suggest that some chemotherapeutic agents may be less effective in estrogen receptor alpha positive (ER+) breast tumors than ER negative (ER-) tumors, which has raised a clinically relevant question as to how to reverse this ER-mediated chemoresistance in ER+ breast tumors. This study is to investigate the possible influence of estrogen receptor alpha (ERalpha) on the therapeutic effects of vinblastine and vinorelbine on breast cancer cells and explore whether combination of anti-estrogen agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
(61 reference statements)
3
28
0
Order By: Relevance
“…Our results provide the first evidence that dovitinib treatment sensitizes FGFR2 mutant cells to pure steroidal selective ER modulators such as ICI182.780. In breast cancer, some authors have reported in vitro and in vivo assays using combinational therapy using ICI182.780 with chemotherapeutic agents such as Doxorubicin (46); Paclitaxel (47), Vinorelbine (48), and Doxotaxel (49), although the results are quite promising, the number of studies is limited and combinational treatment using modern hormone therapy with chemotherapeutic agents has not been examined toughly; specially in endometrial carcinoma treatment. However, several experimental approaches using anticancer kinase inhibitors in tumor cells have revealed numerous feedback loops and have shown that blocking one signaling pathway can block tumor growth partially, but they are not sufficient to cause a complete tumor regression, thereby allowing resistant cells to emerge (50).…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide the first evidence that dovitinib treatment sensitizes FGFR2 mutant cells to pure steroidal selective ER modulators such as ICI182.780. In breast cancer, some authors have reported in vitro and in vivo assays using combinational therapy using ICI182.780 with chemotherapeutic agents such as Doxorubicin (46); Paclitaxel (47), Vinorelbine (48), and Doxotaxel (49), although the results are quite promising, the number of studies is limited and combinational treatment using modern hormone therapy with chemotherapeutic agents has not been examined toughly; specially in endometrial carcinoma treatment. However, several experimental approaches using anticancer kinase inhibitors in tumor cells have revealed numerous feedback loops and have shown that blocking one signaling pathway can block tumor growth partially, but they are not sufficient to cause a complete tumor regression, thereby allowing resistant cells to emerge (50).…”
Section: Discussionmentioning
confidence: 99%
“…E2 also independently activated extracellular signal-regulated protein kinase activity, which contributed to the antiapoptotic effects. In addition, our recent studies also demonstrated that E2 significantly inhibited paclitaxel or vinca alkaloids-induced phosphorylations of bcl-2 and c-raf-1, as well as the degradation of IB in BCap37 cells transfected with ER, which was accompanied with decreased sensitivity of BC-ER cells to the above anticancer drugs (7,8). In response to various extracellular and intracellular signals, p53 mediates cellular processes, such as apoptosis, cell cycle arrest, and senescence, depending on the signal and the cellular context (49)(50)(51).…”
Section: Role Of Apoptosis-related Molecules In Er-mediated Chemoresimentioning
confidence: 83%
“…Neoadjuvant chemotherapy has a well-established role in the management of early-stage, operable breast cancer, and remains the gold standard downstaging systemic therapy in many centers, regardless of ER status. However, the data from other clinical trials or retrospective analyses suggest that ER status might also affect the efficacy of chemotherapy (5)(6)(7)(8). Specifically, it has been observed that some chemotherapeutic agents may be less effective in patients with ER+ tumors than those with ER-tumors.…”
Section: Role Of Estrogen and Estrogen Receptors In Chemoresistance 507mentioning
confidence: 99%
See 2 more Smart Citations